Efektivitas Blended Learning terhadap Hasil Belajar Sains: Systematic Literature Review - I Wayan Karmana (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Blended learning is a learning model that integrates face-to-face learning with online learning to create a more flexible, interactive, and student-centered learning experience. This study aims to analyze the effectiveness of blended learning on science learning outcomes through the Systematic Literature Review (SLR) approach. The study was carried out by referring to the PRISMA guidelines through the stages of identification, screening, feasibility assessment, and inclusion. Literature searches were conducted on Scopus, ScienceDirect, ERIC, Google Scholar, and SpringerLink databases with a publication range of 2019–2025. Based on the selection process, as many as 19 articles met the inclusion criteria and were analyzed using narrative synthesis. The results showed that 84.2% of studies reported that blended learning significantly improved science learning outcomes compared to conventional learning, while 15.8% of studies found no significant difference despite showing an increase in student motivation, engagement, and learning satisfaction. In addition to improving cognitive learning outcomes, blended learning also contributes to improving critical thinking skills, problem solving, science literacy, science process skills, and learning independence. The effectiveness of the implementation of blended learning is influenced by the quality of learning design, teacher competence, student readiness, and technological infrastructure support. These findings show that blended learning is an effective learning strategy to improve the quality of science learning at various levels of education, with the record that its implementation is supported by systematic planning and optimal use of technology.